Prevalence and incidence of sarcoidosis in Korea: a nationwide population-based study - Hee-Young Yoon (Respiratory Research, 2018)
Abstract Background The prevalence and incidence of sarcoidosis varies worldwide. We estimated the prevalence and incidence of sarcoidosis in Korea using nationwide claims data from the Korean Health Insurance Review and Assessment Service. Methods Cases of sarcoidosis were identified for any visit between 2007 to 2016 that listed the Korean Classification of Disease, 7th edition code of sarcoidosis and rare incurable disease exempted calculation code. A narrow case definition was used as follows: 1) ≥ two sarcoidosis-coded visits within 1 year of the first claim, 2) no claims for other diseases that could form granuloma. Results A total of 4791 patients (narrow, n = 2388) visited medical institutions for sarcoidosis during the study period; 2999 patients (narrow, n = 1696) were newly identified between 2009 and 2015. The sarcoidosis prevalence was 9.37 per 105 people (narrow, 4.69) and was highest between ages 60–69 years. The incidence rate was 0.85 per 105 population at risk (narrow, 0.48), with the highest incidence rate between ages 50–59 years. For incident cases (mean age: 48.5 year), the age distribution in whole population and females showed monophasic patterns peaking at aged 50–59 years, while males had biphasic incidence peak at aged 30–39 years and 60–69 years. The annual incidence rates showed increasing trends from 0.85 per 105 population at risk in 2009 to 0.97 per 105 population at risk in 2015. Conclusions In comparison with previous reports, the prevalence and incidence of sarcoidosis in Korea have increased and middle-aged women showed the highest risk.